2018
DOI: 10.12659/msm.908979
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Adenomyosis with Subcutaneous Etonogestrel Implants: A Clinical Observational Study in 17 Patients

Abstract: BackgroundAdenomyosis is a cause of chronic pelvic pain in women of reproductive age. The aim of this study was to investigate the effects of subcutaneous etonogestrel implantation on adenomyosis.Material/MethodsA clinical observational study included 17 women with adenomyosis who were treated with subcutaneous etonogestrel implants and followed-up for 12 months. Imaging and clinical observations were undertaken in the 17 patients at baseline (time 0), and at 3 months, 6 months, and 12 months following subcuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
(14 reference statements)
1
7
1
Order By: Relevance
“…One previous study has suggested that Etonogestrel implants may reduce the uterine volumes of adenomyosis patients. [ 12 ] However, according to data gathered in this study, we did not find any significant change in uterine volumes after treatment.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…One previous study has suggested that Etonogestrel implants may reduce the uterine volumes of adenomyosis patients. [ 12 ] However, according to data gathered in this study, we did not find any significant change in uterine volumes after treatment.…”
Section: Discussioncontrasting
confidence: 50%
“…[ 9 11 ] Nevertheless, fewer studies were found in patients affected by adenomyosis, and all these studies were limited in sample size and follow-up time. [ 12 ] So, it did not allow us to draw a firm conclusion about the topic.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, adenomyosis may be associated with recurrent abortion, premature delivery, and complications of late pregnancy such as placenta previa 38. Drug therapy includes gonadotropin-releasing hormone agonists (GnRHa), oral contraceptive pills (OCs), levonorgestrel-releasing intrauterine devices (LNG-IUS or Mirena), high-dose progestins, danazol, aromatase inhibitors, and selective estrogen/progesterone receptor modulators can relieve symptoms effectively,911 but these drugs are only temporary, and pregnancy is not possible during drug therapy. In addition, some patients are refractory to drug therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Mean visual analogue scores for dysmenorrhoea fell significantly in the ENG-IMP group, but not in the control group over the 12-month study period. In a small prospective cohort study57 of use of the ENG-IMP by 17 women with adenomyosis-associated dysmenorrhoea, all participants reported reduced dysmenorrhoea by 3 months after insertion; mean visual analogue pain score was statistically significantly lower at 3 months than at baseline, with the improvement maintained at 12 months. Almost a third of the participants were amenorrhoeic at 12 months and a quarter reported infrequent bleeding.…”
Section: Non-contraceptive Benefits Associated With Use Of the Etonmentioning
confidence: 94%